Determinants and Motivators of Dividend Policy: A Study of Cement Industry of Pakistan - Islam, Talat; Aamir, Muhammad; Ahmad, Ashfaq; Saeed, Muhammad (Mediterranean Journal of Social Sciences, 2012)
Dividend is one of the most debatable topics for the researchers. Many researchers explore the factors of dividendpolicy. The aim of the study is to find out the factors that motivate the dividend policy among the cement industry. For thepurpose data of eight firms was collected from Karachi Stock exchange and State bank of Pakistan. SPSS 17 was used toanalyze the data and it was found that PE ratio, EPS growth and sale growth are positively associated with the dividend payoutwhile profitability and debt to equity were found to have negative association with dividend payout.